Ameloblastoma in Siriraj Hospital: A 14-Year Retrospective Analysis of Clinicopathological Characteristics Correlating to the WHO 2017 Classification - Yotchai W. (2023)
Background : Ameloblastoma is a benign, locally aggressive neoplasm eliciting frequent relapse and morbidity. Based on many updates, there is an introduction of the World Health Organization (WHO) 2017 Classification in which the terminology has been modified and re-categorized. Objective : To study natural courses, the clinicopathological characteristics, and rate of recurrence of ameloblastoma patients in Siriraj Hospital. Materials and Methods : The H&E stained slides of 122 patients diagnosed with ameloblastoma between 2006 and 2019 at Siriraj Hospital were reviewed and re-classified according to the WHO 2017 Classification. The natural course of disease and the clinicopathological characteristics were analyzed. A descriptive statistical analysis was used to calculate the frequency and percentages of different variables. Results : There were 86.9% of the cases being conventional ameloblastomas, whilst the predominant histologic pattern being the follicular pattern. The treatment of choice is excision. Recurrence of ameloblastoma is thought to be the consequence of several risk factors, clinicoradiological characteristics of the tumor, anatomical locations, treatments of choice, tumoral behavior, and tumor subtypes in particular. Thirty cases presented with recurrence, of which 83.3% were conventional ameloblastomas. Most of the cases were treated with radical treatment and have free surgical resection margins. Conclusion : The clinicopathological characteristics and natural course of ameloblastoma patients in Siriraj Hospital corresponds to the WHO Classification. The present study demonstrated a high recurrence rate in patients treated with conservative surgery. Thus, the authors agree with the WHO 2017 Classification that radical surgery is recommended for patients with a history of recurrence and some specific subtypes of ameloblastomas.